Systemic regulatory factors of angiogenesis in multiple uterine myoma - V. I. Konenkov; A. V. Shevchenko; V. F. Prokofiev; E. G. Koroleva; Yu. S. Timofeeva; S. V. Aidagulova; I. O. Marinkin (Медицинская иммунология)
Uterine leiomyomas (UL) are benign uterine tumors. Hypertrophic increase in muscle mass in LM is accompanied by development of vascular networks, which are regulated by the balance of pro-angiogenic factors, e.g., VEGF-A. Moreover, a number of inflammatory molecules exert pro-angiogenic effects, especially, IL-1β, IL-8, etc. The spectrum of their activity may overlap, being regulated by other cytokines. The aim of our work was to assess serum concentrations of cytokines actively involved in vascular network growth in the patients with multiple uterine fibroids, as compared with data obtained in conditionally healthy women. The survey included 178 females: 89 women (23-60 years old) with uterine fibroids, and 89 conditionally healthy age-matched women (22-61 years old). The levels of TNFα, IL-1β, IL-4, IL-6, IL-8, IL-10 and VEGF-A were detected by ELISA technique (Vector-Best, Russia). Statistical analysis was carried out using the IBM SPSS Statistics 23 (USA). Serum levels of IL-6, TNF and IL-8, were higher among patients compared with healthy women. The dependence of VEGF level on the number of myoma nodes has been established: VEGF serum level was higher in patients with multiple tumor nodes. In healthy women, an increase in TNFα level showed direct correlation with higher serum level of IL-6. Correlation with VEGF level was weakly negative. In leiomyoma, these relationships persist for IL-6, IL-8, VEGF levels. The obtained data are of practical importance not only as potential prognostic criteria for development of the uterine myoma at preclinical stage, but also as additional laboratory indexes for differential diagnostics, in particular when discerning uterine leiomyoma, the most common benign myomatous tumor of uterus, from malignant uterine leiomyosarcomas.